تصور بیعت" فکرولی اللہی "کے تناظر میں(القول الجمیل فی بیان سواء السبیل کا خصوصی مطالعہ): Concept of allegiance in "Waliullah e Thinking" (Special Study of al-Qoul ul Jamil fi bayan Siwus Sabeel) - Mustafa, Hafiz Ghulam; Aziz, Hafiz Abdul (Al-Irfan, 2024)
Al - Qul Al Jamil fi Byan e swa Al sabeel is a well known Book written by The great intellectual and spiritual islamic scholar of the subcontinent Shah Waliullah Muhddsa e Dehlvi. The book deals with the significance, real concept and all information about bayt. The true sufisim which is cause of forgiveness, self-respect, and purification is also called Bayt. Bayt is an effective means of attains spirituality which creates the quality of remembrance of Allah Almighty in a Muslim. Bayt infect is an agreement which a Sheikh took his followers to avoid them from all kinds of misdeeds, evils and displeasures of Allah Almighty. There are many examples of bayt in islamic history. The Holy Prophet took bayt from His companions on different occasions .In this study we will discuss the details of bayt .key words: Bayt, Shah walliullah, spirituality .